Preparation and mechanism of polyurethane prepolymer and boric acid co‐modified phenolic foam composite: Mechanical properties, thermal stability, and flame retardant properties. (12th April 2019) - Xu, Wenzong; Chen, Rui; Xu, Jiaying; Wang, Guisong; Cheng, Chuanming; Yan, Hongyi
Abstract : In this work, a new kind of co‐modified phenolic foam was synthesized with polyurethane prepolymer (PUP) and H3 BO3 by a simple preparation method. Firstly, in order to determine the optimal amount of PUP, the effects of different PUP additions on the mechanical properties, foam microstructure, and pulverization rate of phenolic foam were investigated. Then H3 BO3 was added to toughened phenolic foam, in order to reduce its fire hazard. The results showed that the mechanical properties of the PFPUP8 phenolic foam composite were the best when the PUP content was 8 wt%. It had a small and regular cell structure, and its pulverization ratio was reduced by 80% compared with that of pristine phenolic foam. Meanwhile, the flame retardant properties of PFPUP8 were improved in different degrees with an increase in the amount of H3 BO3 . Particularly, when the addition of H3 BO3 was 10 wt%, the peak heat release rate, the total heat release, and the total smoke release values of PFPUP10B were decreased by 35.4%, 42.4%, and 45.2%, respectively, compared with those of PFPUP8. The value of the limit oxygen index was increased by 33.1%. Besides, the addition of H3 BO3 had no adverse effect on the mechanical properties and pulverization ratio of PFPUP8. In addition, the specific mechanisms of toughening, flame retardant, and smoke suppression are also discussed in this paper on the basis of an investigation into the thermal properties of the toughened flame retardant foam composites by thermogravimetric analysis in N2 atmosphere.